1997
DOI: 10.1080/00032719708007228
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Sulfur(IV) Solutions in the Presence of Amines and the Tendency of Sulfite Ions to Disproportionate in Stock Solutions

Abstract: Several sulfite solutions at the level of 0.050 mo1.L-l were kept at 25"C, in polyethylene flasks, in the presence and absence of air. The concentration of sulfite 1424 GUEKEZIAN ET AL.was periodically checked by the iodometric method. The presence of ethanolamine, ethylenediamine or tris(hydroximethyl)aminomethane, at 0.05 -0.20 rno1.L-l concentration levels, showed a remarkable stabilizing effect at pH values higher than 10.5. The amine ionization was supressed by the common ion effect by using OH-. added as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 21 publications
2
37
1
2
Order By: Relevance
“…TRIS stabilizes S(IV) in solution [2,3]. We have found that there was one small difference on the reaction rate and absorbance limit as the solution B (a mixture of TRIS and S(IV)) ages.…”
Section: Influence Of Sulfur(iv) and Manganese(ii) Concentrationsmentioning
confidence: 83%
See 2 more Smart Citations
“…TRIS stabilizes S(IV) in solution [2,3]. We have found that there was one small difference on the reaction rate and absorbance limit as the solution B (a mixture of TRIS and S(IV)) ages.…”
Section: Influence Of Sulfur(iv) and Manganese(ii) Concentrationsmentioning
confidence: 83%
“…Initiation of the oxidation of Co(II) induced by HSO 3 − , in the absence of added Mn(II) or Fe(III), is due primarily to low concentrations of Fe(III), present as unavoidable impurities in chemicals and even in highly purified water. Co(III) can also be formed by the slow spontaneous oxidation of Co(II) by dissolved oxygen (Equation (1), Figures 1(b) and 2(a)).…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable among these is sulfite disproportionation to form sulfate and thiosulfate (38,39). The rate of this reaction is not well known at seawater temperatures but is critical in determining the concentration of marine sulfoxy anions and in delivering S MIF from atmospheric SO 2 to these sulfur species.…”
Section: Resultsmentioning
confidence: 99%
“…We now need to calculate the number of sulfur atoms expected in the atmosphere and ocean to compare to the critical value given by equation (22) to determine whether observable SO 2 buildup or haze formation is reasonable. This calculation is simplified because aqueous HSO 3 and(/or) SO 3 2are not thermodynamically stable (Karchmer 1970;Hayon et al 1972;Brimblecombe and Lein 1989;Guekezian et al 1997;Jacobson et al 2000;Ermakov et al 2001;Halevy 2013). Spontaneous or easily catalyzed disproportionation and oxidation reactions convert sulfur from S(IV) to S(VI) and/or S(0) (Karchmer 1970; Guekezian et al 1997;Johnston 2011;Halevy 2013), the former even in the absence of dissolved oxygen (Guekezian et al 1997;Zopfi et al 2004).…”
Section: Expected Sulfur In Surface Reservoirmentioning
confidence: 99%